A prospective study comparing Total Lymphocyte Count (TLC) and CD4 counts in HIV patients in a resource limited setting in India - Lal, Lincy; George, Cijo; Yesoda, Anitha; B, Jayakumar (Indian Journal of Pharmacy Practice)
Even after 25 years of the first detection of Acquired Immunodeficiency Syndrome (AIDS), it remains a major health care problem without any cure. Extensive research around the world and the subsequent introduction of highly active antiretroviral therapy (HAART) has produced dramatic reduction on morbidity, mortality and health care utilization. HAART regimens have revolutionized the treatment of human immunodeficiency virus (HIV), which consistently results in sustained suppression of HIV-1 RNA replication, resulting in gradual increases in CD4 T lymphocyte count, sometimes to normal levels.